1965
DOI: 10.1037/h0093880
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the role of salivary secretions in the regulation of food and fluid intake in the white rat.

Abstract: Observations on the food and water intake, specific hunger, and taste preference behavior of rats made desalivate by ligation of the principal salivary ducts are described. Desalivate rats drink excessive amounts of water when feeding on a dry diet, which is attributed to the use of drinking water as an exogenous saliva to facilitate the swallowing of dry food. The feeding pattern of desalivate rats is strikingly similar to that seen in animals recovered from lateral hypothalamic lesions, suggesting that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
1

Year Published

1970
1970
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 36 publications
4
38
1
Order By: Relevance
“…Although the finding that desalivated rats show greater saline preference than the controls validates Vance's (1965) previous observations to this effect, we also found that the group differences disappear after a number of test sessions. It is impossible to ascertain whether the disappearance of group differences was due to successive exposure to the twobottle situation or to the possibility that postoperative effects may be minimized after a certain period after the operation.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Although the finding that desalivated rats show greater saline preference than the controls validates Vance's (1965) previous observations to this effect, we also found that the group differences disappear after a number of test sessions. It is impossible to ascertain whether the disappearance of group differences was due to successive exposure to the twobottle situation or to the possibility that postoperative effects may be minimized after a certain period after the operation.…”
Section: Resultssupporting
confidence: 74%
“…We feel that it is necessary to validate Vance's (1965) results under conditions more' amenable to statistical analysis. The present experiment was designed to compare the isotonic saline intake of desalivated and sham-operated rats over a number of days once the operation was completed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Desalivation in rats, on the other hand, does lead to an excessive water intake when the animals are feeding on a dry diet (Epstein et al, 1964;Vance, 1965). In this case, the increased "thirst" is associated with an exaggerated prandial drinking, the animals using large amounts of drinking water to facilitate the swallowing of dry food.…”
mentioning
confidence: 99%